VALIDITY OF THE STANDING SPIKE TEST AS A MONITORING PROTOCOL FOR FEMALE VOLLEYBALL PLAYERS - Jose Manuel Palao; David Valades (Biology of Sport, 2012)
The purpose of this paper was: a) to provide reference values for the standing spike test for female volleyball players and b) to study whether the standing spike test is valid for assessing the theoretical differences between female volleyball players. The sample included 83 players from the first nine teams of the Spanish women’s first volleyball division (52 Spanish players and 31 from other nationalities). The variables studied were the ball speed of the standing spike test, the age of the players, the player’s role (outside hitter, opposite, middle-blocker, libero, or setter), height, and nationality of the players (Spanish or foreign). The results demonstrate the ranges for the standing spike among female performance volleyball players (70-82 km · h-1). The differences regarding nationality, player role, height, and age seem to indicate that the test is a valid instrument for monitoring the performance of female volleyball players.